1996
DOI: 10.1097/00005650-199602000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Determine the Treatment for Local and Regional Prostate Cancer

Abstract: This article assesses the significance of comorbid and nonclinical factors in type of treatment received by elderly male patients with local-regional stage prostate cancer. Multivariate analysis of data from the Virginia Cancer Registry was linked to Medicare claim files, the Area Resource File, and 1990 Census Data. The type of initial treatment received was studied in 3117 men with local-regional staged prostate cancer diagnosed from 1985 to 1989. The frequency of surgical and radiation therapy for prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 19 publications
4
62
1
1
Order By: Relevance
“…These results confirm earlier findings 6,7 that receiving aggressive treatment for prostate carcinoma is less likely with certain comorbidities or increasing comorbidity scores; a study that compared any treatment and no treatment found a similar relation. 13 However, we found that surgery and radiation treatment may be related to different factors and should therefore be assessed separately. We also found that the effects of comorbid conditions may vary according to other risk factors, such as presenting symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…These results confirm earlier findings 6,7 that receiving aggressive treatment for prostate carcinoma is less likely with certain comorbidities or increasing comorbidity scores; a study that compared any treatment and no treatment found a similar relation. 13 However, we found that surgery and radiation treatment may be related to different factors and should therefore be assessed separately. We also found that the effects of comorbid conditions may vary according to other risk factors, such as presenting symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…17,28,29 With regard to prostate cancer-specific survival and SES, we found an 11% unadjusted survival difference between men of low versus high SES. The excess mortality risk associated with low SES remained significant, even after adjusting for tumor characteristics at diagnosis.…”
Section: Gleason Gradementioning
confidence: 79%
“…15 Many previous studies regarding SES and prostate cancer mortality are from North America, particularly from the United States, in which the area code generally is used as surrogate of individual level of SES. 8,9,12,13,16,17 In addition, SES measures may have different meanings in different populations. 15 Furthermore, to our knowledge, few studies to date have evaluated factors impacting social disparities in prostate cancer mortality, such as differences in screening, disease stage at diagnosis, tumor characteristics, and treatment.…”
mentioning
confidence: 99%
“…Data from the Virginia Cancer Registry on 3117 men with local-regional prostate cancer diagnosed between 1985 and 1989 also showed that age, even after adjustment for co-morbidity, was the strongest predictor of treatment. 6 In a population-based study carried out in the southern part of the Netherlands between 1993 and 1996, treatment decisions were also determined largely by the patient's age and the experience of the urologist, instead of the patient's co-morbid conditions. 10 In contrast, other studies found that patients with co-morbidity were treated less aggressively (after adjustment for age).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent population-based study in the registration area of the Eindhoven Cancer Registry, the prevalence of at least one co-morbid disease increased from 33% of patients younger than 60 years to 58% of patients aged 80 years or older. 2 Older patients with co-morbidity are often treated less extensively, [3][4][5][6] probably because these patients have a shorter life expectancy and an increased risk of complications. [7][8][9][10] Treatment results for elderly prostate cancer patients are largely unknown, as most of these patients are excluded from clinical trials.…”
Section: Introductionmentioning
confidence: 99%